The Role of Nickel in Low Alloy Steels exposed to H2S-containing environments. Part I: Trench Formation at the Open Circuit Potential - Chalfoun, Dannisa Romina (2023)
The nickel content in low alloy steels (LAS) for oil and gas exploration and production is limited to a maximum of 1 wt.% according to ANSI/NACE MR 0175/ISO 15156. This restriction is imposed to avoid sulfide stress cracking (SSC) in sour (H2S-containing) environments. In this work, the effect of Ni on SSC of LAS was studied independently of other alloying elements. For this purpose, quenched and tempered steels heat treated to a yield strength of 610 MPa with a Ni content below and above the 1 wt.% threshold were evaluated at the open circuit potential (OCP) in unstressed specimens, and in slow strain rate tests (SSRT) at room temperature. Thiosulfate was used as a surrogate of H2S, according to the Tsujikawa method. It is concluded that Ni contributes to the stabilization of the sulfide films that form on the steel´s surface at OCP. The rupture of this film due to tensile stress promotes the nucleation of elongated deep pits, referred to as trenches, which can act as sulfide stress crack initiators. Trenches were observed exclusively in stressed, Ni-containing specimens. Moreover, trenches´ morphology, dimensions, and distribution varied with the Ni content in the steels. For the steels studied in this work, the Ni effect on trenching persisted below the 1 wt.% threshold.